2016
DOI: 10.1038/jhh.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of undiagnosed and uncontrolled hypertension: observations from a poor-resource setting

Abstract: Early detection is the cornerstone of hypertension management; still majority remains undetected until complications arise, especially in poor-resource settings. Paucity of information regarding undiagnosed and uncontrolled hypertension in eastern India thus called for a detailed investigation involving a representative sample of adults in Malda, one of the poorest districts in the region. In a cross-sectional study, between October 2013 and July 2014, using multistage random sampling with probability-proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
2
22
3
5
Order By: Relevance
“…On the other hand, the results of other studies showed that patients aged younger than 60 years were more likely than older patients to have controlled BP. 12,21,27,45,[49][50][51] This was due to with increasing age, there will be increasing stiffness of the aorta and arterial walls which contribute to the observed high prevalence of HTN in the older group. 12,45,52 Thus, ongoing surveillance to determine trends in BP overage is necessary to provide a basis for evaluating and guiding public health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of other studies showed that patients aged younger than 60 years were more likely than older patients to have controlled BP. 12,21,27,45,[49][50][51] This was due to with increasing age, there will be increasing stiffness of the aorta and arterial walls which contribute to the observed high prevalence of HTN in the older group. 12,45,52 Thus, ongoing surveillance to determine trends in BP overage is necessary to provide a basis for evaluating and guiding public health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Development and Social Inclusion was in charge of the development of the questionnaires and assessments [ 14 ]. The Peruvian National Institute of Statistic and Informatics was in charge of the data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in Peru have described a great gap between diagnosis, treatment, and control of hypertension [ 13 ] and reports worldwide show that the gap increases in settings with fewer resources (33% more awareness of hypertension in people with higher socioeconomic status in comparison to lower socioeconomic status) [ 14 ]. Poverty leads to less access to healthcare, less awareness, and treatment of hypertension, if an association with cognitive impairment is found, is possible that the magnitude of this association would be higher in comparison to other values found in previous studies in not deprived populations.…”
Section: Introductionmentioning
confidence: 99%
“…Older age (>60 years) and obesity are two factors that are consolidated in the literature as predictors of reduced BP control . However, when the association analysis was performed according to sex, it was observed that only younger age in women (<60 years) was associated with better BP control.…”
Section: Discussionmentioning
confidence: 99%
“…Older age (>60 years) and obesity are two factors that are consolidated in the literature as predictors of reduced BP control. 6,[23][24][25][26] However, when the association analysis was performed according to sex, it was observed that only younger age in women (<60 years) was associated with better BP control. In contrast, in men, there was a lower percentage of younger patients with controlled BP, although this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%